Three-Dimensional High-Resolution Laser Lithography of CsPbBr3 Quantum Dots in Photoresist with Sub-100 nm Feature Size - Boyuan Cai; Haoran Jiang; Run Bai; Shengting Zhu; Yinan Zhang; Haoyi Yu; Min Gu; Qiming Zhang (Nanomaterials)
Perovskite quantum dots (PQDs), with their excellent optical properties, have become a leading semiconductor material in the field of optoelectronics. However, to date, it has been a challenge to achieve the three-dimensional high-resolution patterning of perovskite quantum dots. In this paper, an in situ femtosecond laser-direct-writing technology was demonstrated for three-dimensional high-resolution patterned CsPbBr3 PQDs using a two-photon photoresist nanocomposite doped with the CsPbBr3 perovskite precursor. By adjusting the laser processing parameters, the minimum line width of the PQDs material was confirmed to be 98.6 nm, achieving a sub-100 nm PQDs nanowire for the first time. In addition, the fluorescence intensity of the laser-processed PQDs can be regulated by the laser power. Our findings provide a new technology for fabricating high-resolution display devices based on laser-direct-writing CsPbBr3 PQDs materials.